Designed antiviral ankyrin – A computational approach to combat HIV-1 via intracellular pathway by targeting the viral capsid of HIV-1 - Hana Atiqah Abdul Karim (2019)
© 2018 Elsevier B.V. Scaffold known as designed ankyrin repeat proteins (DARPins) have been utilized by scientists extensively in protein binding, as they acquire remarkable binding properties. Trimodular ankyrin repeat protein (Ank1D4) is a potential macromolecular and antiviral intracellular inhibitor that aims the N-terminal domain capsid protein (NTD CA ) of viral Human Immunodeficiency Virus type-1 (HIV-1) at the virus assembly and budding machinery process. The protein-protein interaction between Ank1D4 and the viral capsid CA alpha helixes H1 and H7 have been studied in depth and point mutation strategy at the S45 1D4 key residue position was conducted to further improve the binding interaction and efficacy on the wildtype Ank1D4 structure with NTD CA . A computational approach via molecular dynamics (MD) simulation has been fully utilized in this study to simulate both the wildtype and potential novel complexes. Free energy contributions on the modified Ank1D4-NTD CA (H1, H7) complexes were acquired by using vigorous scoring functions of implicit solvent models; Molecular Mechanics/Poisson-Boltzmann surface area (MM-PBSA) and Molecular Mechanics/Generalized Born surface area (MM-GBSA), respectively. The wildtype structure of Ank1D4-NTD CA H7 has been proven to possess better binding stability than the H1 complex. From there, two mutants of H7 complex were generated and the computed ∆G bind values based on both models have revealed that S45Y-H7 has the lowest binding free energy compared to both S45W-H7 and S45-H7 (Wildtype). The binding strength predictions given by both MM-PBSA and MM-GBSA in the following ranking order for the three systems in terms of the value of ∆G bind : S45Y-H7 > S45 W-H7 > S45-H7. These findings provide a good basis in directing us a step further to discover better novel treatment modalities to treat millions of HIV-1 patients.